Difusão de tecnologia CAD e CNC como ferramenta básica de criação e produção em pequena escala, acessível à comunidade - Hellmeister, Luiz Antonio Vasques [UNESP]; Marar, João Fernando [UNESP]; Sementille, Antônio Carlos [UNESP]; Freitas, João Paulo de Oliveira [UNESP] (My University, 2011)
The high competitiveness and the search for newtechnologies that differentiate the product from the project,require the use of new digital tools. The computer aideddesign - Computed Aided Design (CAD), with electronicmodeling, simulation, structural analysis and production,performed in a virtual environment through the applicationof specific software, are available but their use is stilllimited. There are various software available in languagesand extensions to industrial production which, from 3Dmodeling, they can manage through Computer NumericalControl - Computed Numerical Control (CNC) machiningcenters, laminating, stamping, mold making and otherprocesses productive. This project aims to encouragecreativity and entrepreneurship in the community throughthe provision of technology computer aided design - CAD,with a view to implementation of machining technology.
Keywords: CAD; CNC; Application; Creativity